PERSAINGAN CHINA-AUSTRALIA DALAM PEREBUTAN PENGARUH DI KAWASAN PASIFIK - Siti Nadjiha Hariri (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2020)
The rise of China in the Pacific region is a threat to Australia as a traditional actor who has an important influence and role in the region. The rise of China pushed Australia to increase its role in the region. The Australian Government responded by channeling funds to Pacific countries to build infrastructure, a step taken by the Australian government is considered to counteract China's influence in the Pacific. With a series of major investment funds and development assistance projects, Australia and China are trying to compete with each other to create a network of their power and influence in the Pacific countries. This journal discusses the role of China-Australia in the competition for influence in the Pacific Region, using qualitative methods aimed at describing and analyzing a phenomenon systematically. This method will explain how China's role in the Pacific region increases and Australia's response as one of the traditional actors in the region. The discussion in this journal is the influence of Australia in the Pacific, the increasing role of China and Australia's response to China's rise in the Pacific Region. Keywords: Australia, China, Pacific Islands Abstrak Kebangkitan Cina di kawasan Pasifik menjadi khusus bagi Australia sebagai aktor tradisional yang memiliki kepentingan dan peran penting dikawasan. Kebangkitan China mendorong Australia untuk meningkatkan kembali perannya dikawasan. Pemerintah Australia merespons dengan akan menyalurkan dana ke negara-negara Pasifik untuk membangun infrastruktur, langkah yang diambil oleh pemerintah Australia ini guna untuk menangkal pengaruh Cina di Pasifik. Dengan bantuan dana investasi utama dan proyek-proyek bantuan pembangunan, Australia dan Cina berusaha saling berlomba-lomba untuk menciptakan jaringan koordinasi dan memfasilitasi mereka di negara-negara Pasifik. Jurnal ini membahas tentang Peran Cina-Australia dalam Persaingan pengaruh di Kawasan Pasifik, dengan mengunakan metode kualitatif yang membahas dan menganalisa fenomena yang sistematis. Metode ini akan menjelaskan cara meningkatkan peran Cina dikawasan Pasifik serta respons Australia sebagai salah satu aktor tradisional di kawasan. Terkait pembahasan dalam jurnal ini yaitu Australia di Pasifik, Peran Cina juga respons Australia terhadap China di Kawasan Pasifik. Kata Kunci: Australia, China, Kepulauan Pasifik